Formation of the Accumulative System of Compulsory State Pension Insurance in Ukraine - Mykhailo KUZHELIEV; Valerii PAVLIUK; Vita FEDYNA; Alina NECHYPORENKO (Communications of International Proceedings, 2020)
Purpose: This article is dedicated to the formation of a pension system based on fundamentally new accumulative principles. Each state applies its own model of accumulative system. The future of senior citizens, which, in the conditions of demographic distortion, makes up a significant percentage of the population, depends on how balanced its construction is. Methodology: The following research methods and techniques were applied during the study: evaluation and data processing, statistical method, study of economic processes, determination of patterns and trends in their development, identification of areas of further improvement of these processes. Conclusions: Assessment of the parameters of the introduction of the accumulative component of pension insurance allowed to determine the advantages and disadvantages of the chosen model in Ukraine. Special attention should be paid to the factors, that will affect the efficiency of the system: the architecture of the system; macroeconomic situation; the state of the domestic stock market; level of administrative costs; problem of securing the money savings of citizens. Implications: The accumulative system is vulnerable to economic and financial risks, which requires special care in developing the conceptual framework for its implementation and paces additional responsibility on the government for the consequences of such steps.
Keywords: Pension Reform; Accumulative Pension System; Legislative Proposal; Pension Treasury; Investment Potential.